Opinion of hepatic transplant waiting list patients regarding split liver transplantation - de Faria, E. Petribu [UNESP]; Llanos, Juan Carlos [UNESP]; Bakonyi Neto, Alexandre [UNESP]; Silva, A. P. C. [UNESP]; Winckler, C. C. [UNESP]; Mutti, A. [UNESP]; Saad-Hossne, R. [UNESP]; Silva, Giovanni Faria [UNESP]; Gomes, M. R. B. [UNESP]; de Paula, R. C. Callile [UNESP]; Biagioni, D. S. [UNESP]; Almeida, Ricardo Augusto Monteiro de Barros [UNESP]; et al. (Elsevier B.V., 2008)
Background. Split liver transplantation (SLT) increases organ supply for hepatic transplantation. Long-term patient survival and complication rates seem to be equivalent between orthotopic liver transplantation (OLT) and SLT. There are controversies among transplant physicians due to an ethical dilemma between benefiting individual needs or those of society. Barshes and Goss (Am J Transplant 5:2047, 2005) demonstrated that the majority of adult liver transplant candidates are favorable to SLT. The aim of our study was to evaluate the opinions of patients at a Brazilian university hospital regarding SLT.Materials and Methods. A questionnaire with 14 questions was applied to 50 patients included in a hepatic transplant waiting list regarding SLT.Results. The overall attitudes of 66% of the participants were classified as utilitarian, 31% were classified as self-preserving, and 3% were undecided. Ninety-one percent of patients would be willing to share even if their expected survival after SLT was shorter than that with OLT. For 77% of patients, children must have priority over adults. However, 83% were unaware of the donors for pediatric transplantations.Conclusions. SLT is a consistent solution for organ demand despite controversies among transplant physicians. The present study demonstrated that most patients were favorable to SLT. In conclusion, attitudes toward graft sharing are not barriers to SLT.